Syphilis: then and now - Plagens-Rotman, Katarzyna; Jarząbek-Bielecka, Grażyna; Merks, Piotr; Kędzia, Witold; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Getting to know the history of syphilis should begin with an attempt to establish the original source of its spread throughout the world. The dispute about the origin of syphilis, a sexually transmitted infection caused by Treponema pallidum (subspecies pallidum), had not been resolved even as late as in the twenty-first century, and to this day the supporters and opponents of the thesis that syphilis was brought to Europe by Christopher Columbus’ sailors have been fighting without solid and sustainable foundations. The French named syphilis “the Neapolitan disease”, while the Italians called it “the French disease”.